Formulation and Evaluation of Topical Dosage Form of Eupatorium Odoratum Linn. and their Wound Healing Activity - PRABHUDUTTA PANDA,; ARPITA GHOSH, (International Journal of Pharma and Bio Sciences, 2010)
Topical application of ointments and gels prepared from the methanol extract of Eupatorium odoratum L (Family-Asteraceae) were formulated and evaluated for its efficacy and safety. Ointments and gels were prepared at different concentrations i.e. 5%, 7.5% and 10%( w/w) by fusion method using different excipients. These topical formulations were tested for pH, viscosity, spreadability, drug contents uniformity, in vitro diffusion. The stability study was carried out at 4, 25 and 370C. The drug content uniformity of ointments and gels were found with in the range of 98.18% to 98.96% and 97.23% to 98.66% respectively. The formulations of O-III and G-III showed maximum drug release of 78% and 90% over a period of 8h. All the formulations were evaluated for its acute skin irritancy, wound healing activity in Swiss Albino rats. These formulations did not produce any skin irritation for about a week when applied over the skin. Comparative studies showed that the viscosity of the formulations increases, spreadability decreases and vice versa. From the stability studies, ointments and gels showed no changes in pH, viscosity, spreadability, extrudability, drug contents, consistency, and phase separation after keeping at different temperatures for 90 days. All the formulations and the normal methanol extracts of Eupatorium odoratum showed significant (P< 0.001) wound healing activity by excision wound model and comparable with that of the reference standards and control bases. The measurement of the wound areas were taken on 3rd, 6th, 9th, 12th, 15th and 18th days and the percentages of wound closures were calculated.